2020
DOI: 10.1177/2309499019900274
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intra-articular fentanyl supplementation for knee arthroscopy: A meta-analysis of randomized controlled studies

Abstract: Introduction: The efficacy of intra-articular fentanyl supplementation for pain control after knee arthroscopy remains controversial. We conduct a systematic review and meta-analysis to explore the influence of intra-articular fentanyl supplementation for pain intensity after arthroscopic knee surgery. Methods: We searched PubMed, EMbase, Web of Science, EBSCO, and Cochrane Library databases through May 2019 for randomized controlled trials (RCTs) assessing the efficacy and safety of intra-articular fentanyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Zeng et al 36 in a meta‐analysis have shown that a single intra‐articular injection of morphine after knee arthroscopy provides better pain relief and reduces the need for supplementary analgesics in the immediate post‐operative period. Similarly, meta‐analytic studies for intra‐articular fentanyl and tramadol have reported better pain relief after knee arthroscopy 8,9 . An RCT has also demonstrated significantly reduced pain scores up to 24 hours with intra‐articular buprenorphine after knee arthroscopy 37 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Zeng et al 36 in a meta‐analysis have shown that a single intra‐articular injection of morphine after knee arthroscopy provides better pain relief and reduces the need for supplementary analgesics in the immediate post‐operative period. Similarly, meta‐analytic studies for intra‐articular fentanyl and tramadol have reported better pain relief after knee arthroscopy 8,9 . An RCT has also demonstrated significantly reduced pain scores up to 24 hours with intra‐articular buprenorphine after knee arthroscopy 37 .…”
Section: Discussionmentioning
confidence: 95%
“…20,35 Zeng et al 36 tramadol have reported better pain relief after knee arthroscopy. 8,9 An RCT has also demonstrated significantly reduced pain scores up to 24 hours with intra-articular buprenorphine after knee arthroscopy. 37 It is important to note that the use of intra-articular opioids in knee procedures have focused on pain relief only in the immediate post-operative period (up to 24 hours after surgery), unlike trials on TMJ arthrocentesis where the focus was on improving outcomes at short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was calculated using Power Analysis and Sample Size software program (PASS) version 11.0.4 using a one-way ANOVA based on previously published results (3,13) about the time to first request of analgesia as the primary outcome. Assuming that SD was 1 and the calculated effect size (f) was 0.43, a sample size of 87 equally divided into three groups can achieve 95% power with a 0.05 significance level.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%